(3eYOdGJ GdfjchJjf ai GdOe h YdGbJgG HGdCOGA Ydi HYV GdhXGFa GdeYQajI (B= s Relationship of nicotine rates in bloodstream to performance on some cognitive functions - (3UGHQjf aJMi YHOGdQMef GdSjOs; (3CejeI eMeO CfhQ (B: s; (3aDGO eMeO CHhGdecGQe (B: s ((3GdbGgQI (B: s (3UGHQjf aJMi YHOGdQMef GdSjO (B: s, 2018)
(3gOaJ GdOQGSI GdMGdjI Gdi aMU GdaQhb Hjf eQJaYi h efNaVi GdGYJeGO Ydi GdfjchJjf (B((3HeDTQGJg GdfaSjI h GdHjhdhLjI(B) (3Ydi cd ef GdGfJHGg h GdPGcQI GdYGedI(B. (3h cTaJ GdfJGFL Yf hLhO aQhb OGdI EMUGFjG Hjf eLehYI GdeONfjf h ZjQ GdeONfjf ai eYOd GdfjchJjf ai GdOe(B: (3h ajeG jJYdb HGdaQhb Hjf eQJaYi h efNaVi GdGYJeGO Ydi GdfjchJjf JHjf Gf gfGc aQhbG HjfgeG ai GdObI h GdSQYI ceDTQGJ GdJQcjR GdGfJHGg ai GJLGg YjfI efNaVi GdGYJeGO Ydi GdfjchJjf(B: (3h cPG JHjf hLhO aQhb Hjf GdeLehYJjf ai ehGUdI GdGfJHGg GdSeYi ai GJLGg YjfI eQJaYi GdGYJeGO(B: (3ai Mjf de JhLO aQhb HjfgeG ai ehGUdI GdGfJHGg GdHUQi(B. (3h ajeG jJYdb HGdPGcQI GdYGedI abO JHjf hLhO aQhb Hjf GdeLehYJjf ai YedjI GdeYGdLI abO cGfJ Cbd caGAI dOi YjfI eQJaYi GdGYJeGO Ydi GdfjchJjf(B: (3ai Mjf de JcTa GdfJGFL Yf hLhO aQhb HjfgeG ai YedjI GdJPcQs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdBOGH (B- (3bSe Yde GdfaSs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdJONjfs; (3GdfjchJjfs; (3eYOd GdfjchJjf ai GdOes